PEMBATASAN JUMLAH PEMBUATAN AKTA NOTARIS OLEH DEWAN KEHORMATAN PUSAT IKATAN NOTARIS INDONESIA - Kartikosari, Heni; Sesung, Rusdianto (Faculty of Law, University of Muhammadiyah Malang, 2017)
To protect the Notary Public Offices and the people who use Notary services related to the legal certainty of the deed made by the Notary, the Central Board of Trustees of the Indonesian Notaries Association issued the Regulation of the Central Board of Honor No. 1 of 2017 on the Fairness Limit of Number of Permanent Deeds. The regulation is determined by the Central Board of Trustees that the limit of fairness in the deed per day is 20 (twenty) deeds. In the fact, there are so many notaries that broke the regulation. So, it must be cleared by a juridical research against that phenomenon. The research method used is normative legal research, that is legal research conducted by examining library materials or secondary law material while in searching and collecting data is done by two approaches, that is law approach and conceptual approach.